PENDAPATAN DAN FAKTOR YANG MEMPENGARUHI PETANI MELAKUKAN FERMENTASI KAKAO DI KABUPATEN JEMBRANA - Hariyati, Yuli (Program Studi Agribisnis Fakultas Pertanian Universitas Dwijendra, 2013)
Cocoa is one of the commodities that may contribute sizeable income countries. In addition, cocoa economy can be a source of farmersâ?? income, create jobs, encourage the activities of agribusiness and agro-industries and develop the economy of the region. Jembrana and Tabanan regency, two districts in Bali which dominates the total area and production of cocoa. Jembrana establish that cocoa plant is a main commodity. The District has been designated as a Fast Growing Region-Based Evolving Cocoa. Cocoa planting area, production and productivity in Jembrana still under ideal that are still being developed.This study aims to assess the fermented cocoa farmers â??income and not fermented and examine the factors that influence farmersâ?? decisions to perform fermentation and to determine differences in the income of cocoa farmers who do not do the fermentation and fermentation. Location of the study in the district of Jembrana by using purposive method. The method used is descriptive method. The selection of respondents using a Multiple Stage Cluster Sampling. This study uses primary data and secondary data. Data analysis methods used are logit models and revenue analysis.The results showed that: (1) there was no difference in the average revenue per hectare between cocoa farmers ferment the cocoa farmers who do not perform fermentation, (2) decision-making fermented cocoa farmers affected by the price of cocoa per kg, farmers farming experience cocoa and participation of farmers in cocoa processing training. As for education level, age of farmers, and the farmers in the group activity has no effect on the decision-making fermentation of cocoa farmers.Keywords: cocoa, fermentation, income, decision making